Historical research - Danto, Elizabeth Ann. (Oxford : Oxford University Press, 2008)
This title guides doctoral students and researchers in the construction of a historical study, from problem formulation to instrument construction to data collection and analysis.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Sociology -- Research -- Methodology; Sociology -- History